FORMULATION AND ANTIOXIDANT ACTIVITY TEST OF SERUM COMBINATION OF MINT LEAVES ATTENTIVE OIL (Mentha piperita L.) AND SPRING FLOWER ATTENTIVE OIL (Clitoria ternatea L.) DPPH METHODS - Maharni, Aulia Prastika; Permata, Bangkit Riska; Wardani, Tatiana Siska (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Mint (Mentha piperita L.) contains key compounds such as menthol and menthone, which have strong antioxidant activity. Butterfly pea flowers (Clitoria ternatea) contain phenolic compounds, flavonoids, anthocyanins, and flavonol glycosides as antioxidants. This study aimed to determine the physical quality of serum preparations and the antioxidant activity of a serum combination of mint leaf essential oil (Mentha piperita L.) and butterfly pea flower essential oil (Clitoria ternatea L.) using the DPPH method. The results of the physical testing of the serum preparations showed that serum formulas F0, F1, F2, and F3 met good physical quality test standards. The antioxidant activity test results for the serum preparation combination of mint leaf essential oil and butterfly pea flower essential oil were as follows: Formula 0 (567.256 ppm), Formula 1 (141.007 ppm), Formula 2 (69.506 ppm), and Formula 3 (133.769 ppm).